MEMORY AND COGNITIVE IMPAIRMENTS FOLLOWING TRAUMA: THERAPEUTIC IMPLICATIONS AND APPROACHES - Okonkwo, Chinwe Victoria; Ricciardi , Francesco Matteo (Research Journal of Health, Medicine and Nursing, 2024)
This study investigates the impact of trauma on memory and cognitive functioning, with a focus on the implications for therapeutic interventions. Using a mixed methods design, the research was conducted in clinical settings involving a sample of 50 individuals who have experienced trauma and 50 who have not, out of a total population of 100 participants. Quantitative data were collected through standardized neuropsychological tests, while qualitative insights were obtained from semi-structured interviews. The results indicate that there is no significant difference in memory performance between individuals who have experienced trauma and those who have not (r = -0.21, p = 0.08), suggesting a weak negative correlation that is not statistically significant. Similarly, the study found no significant relationship between the severity of trauma experienced and cognitive functioning (r = 0.03, p = 0.78), indicating that trauma severity does not appear to influence cognitive functioning in the sample. However, the study did find a significant positive correlation between therapeutic interventions and improved memory and cognitive functioning (r = 0.52, p < 0.001). This suggests that therapeutic interventions designed to address trauma are associated with enhanced cognitive outcomes, highlighting their efficacy in improving memory and cognitive functioning among affected individuals. These findings underscore the importance of therapeutic interventions in supporting trauma survivors, facilitating adaptive cognitive restructuring and promoting psychological well-being